2010
DOI: 10.1103/physreva.81.033844
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherent transients in cold atoms: From free-induction decay to optical precursors

Abstract: We report theoretical and experimental studies of the propagation of a square-modulated laser pulse through a laser-cooled atomic ensemble of two-level absorbers, as well as through a three-level system with electromagnetically induced transparency. We find that the transmission characteristics over a wide range of optical depth can be fully accounted for as optical coherent transients excited by the wide spectral content of the square-modulated optical pulse. We show that both time-domain atom-field coupled e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…They found that the precursors have a large amplitude that is comparable to the amplitude of the incident signal and persist for many nanoseconds for the case when the signal frequency is very close to the resonance frequency of the Lorentz model dielectric ͉͑ c − 0 ͉ Շ ␦͒, making them easier to detect directly using standard fast detectors and oscilloscopes. This research prompted other studies [20], including the generation of optical precursors in a material displaying electromagnetically induced transparency [21,22]; the interplay between optical precursors, selfinduced transparency [23], and free-induction decay [24]; and the so-called precursor stacking [25].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…They found that the precursors have a large amplitude that is comparable to the amplitude of the incident signal and persist for many nanoseconds for the case when the signal frequency is very close to the resonance frequency of the Lorentz model dielectric ͉͑ c − 0 ͉ Շ ␦͒, making them easier to detect directly using standard fast detectors and oscilloscopes. This research prompted other studies [20], including the generation of optical precursors in a material displaying electromagnetically induced transparency [21,22]; the interplay between optical precursors, selfinduced transparency [23], and free-induction decay [24]; and the so-called precursor stacking [25].…”
Section: Introductionmentioning
confidence: 83%
“…5 and 6 will then remain valid, subject to the equivalence relations given in Eqs. (24) and (25), as the medium density is further decreased.…”
Section: Ultrawideband Pulse Dynamics In the Weak Dispersion Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to extract the optical precursors while the main pulse remains. Recently, with the aid of electromagnetically induced transparency (EIT) [15,16], direct observation of precursors, which are separated from the delayed main fields due to the slow-light effect, has been achieved in cold atoms [11,[17][18][19]. Motivated by the observation of precursory spikes at the leading edge of biphoton correlation [20,21], the direct observation of heralded singlephoton precursors with step-and square-modulated wave packets passing through cold atomic EIT medium has been reported [22].…”
Section: Introductionmentioning
confidence: 98%
“…It is difficult to extract the optical precursors while the main pulse remains. With the aid of electromagnetically induced transparency (EIT) [17], optical precursors can be separated from a main pulse through an opaque medium in time [18][19][20]. In this case the precursor signals are significantly ahead of the delayed main pulse due to the slow-light effect.…”
Section: Introductionmentioning
confidence: 99%